"Progressive" Public-Private Partnerships: Are They Reformative or Regressive!?. (October 2022) - Casady, Carter B.; Garvin, Michael J.
In North America, public-private partnerships (P3s) are increasingly using pre-development agreements to enhance collaboration between the public and private sectors. Known colloquially as "progressive P3s", these agreements allow the private sector to help scope and shape the structure of projects at the front end. However, concerns about their efficacy persist. Our Commentary contextualizes this ongoing debate by outlining the potential benefits and pitfalls of this new approach to P3s. We conclude that both practitioners and academics have a crucial role to play in our experience with and understanding of the progressive P3 experiment.